Wage dynamics in Bulgaria: co-movement and causality - Manolova, Hristina; Vasilev, Aleksandar (Sofia University St. Kliment Ohridski, 2017)
"Motivated by recent debates on the possible role of wages as an income policy tool, in this study we examine the dynamic inter-relationship between wages in Bulgaria, mainly in the context of its EU accession. Relative to the WDN studies on the other EU member states, the novelty in this paper is the inclusion of the minimum wage as a possible conditional determinant of the other two wages. We demonstrate that minimum wage increases do not cause changes in average wages in either the government or the private sector. Using variety of econometric tests, we also demonstrate the leadership of private sector wage over public compensation and recommend the implementation of policy measures aimed at labor productivity growth."